2014
DOI: 10.3389/fevo.2014.00022
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sexual signals: calls over colors for mate attraction in an aposematic, color-diverse poison frog

Abstract: Sexual signals indicate species identity and mate quality, and their importance for mate attraction is largely recognized. Recently, research in animal communication has started to integrate multiple signal modalities and evaluate their interactions. However, mate choice experiments across animal taxa have been limited to laboratory conditions, and assessments of multiple sexual signals under field conditions are still lacking. We take advantage of the divergence in visual and acoustic signals among population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 49 publications
(86 reference statements)
0
39
0
1
Order By: Relevance
“…This occurs in the form of female choice on call frequency where spectral call characteristics such as dominant frequency are important to frog evolution (Ryan 1986). Female frogs or toads recognize male of their own species in mating through male mating calls which play an important role in prezygotic isolating mechanism (Dreher & Prohl 2014). Failure to mate might result in offspring reduction that eventually leads to local extinction.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs in the form of female choice on call frequency where spectral call characteristics such as dominant frequency are important to frog evolution (Ryan 1986). Female frogs or toads recognize male of their own species in mating through male mating calls which play an important role in prezygotic isolating mechanism (Dreher & Prohl 2014). Failure to mate might result in offspring reduction that eventually leads to local extinction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed color-assortative mate preferences Cummings, 2008, 2009) but disregarded the potential relevance of acoustic signals. Dreher and Pröhl (2014) found that acoustic signals, that is, male advertisement calls, were more important in female choice than color patterns. Across populations, females preferred local to non-local advertisement calls, largely unaffected by the simultaneous presentation of local and non-local color morphs of the calling males.…”
mentioning
confidence: 97%
“…Most strikingly, Dreher and Pröhl (2014) observed that differences in advertisement calls were associated with genetic divergence, whereas color patterns varied within genetic groups. The strength of acoustic preference for local calls varied among populations, which might indicate different stages of prezygotic behavioral isolation, from loose to almost complete.…”
mentioning
confidence: 98%
See 2 more Smart Citations